Long-term effects of binary mixtures of 17α-ethinyl estradiol and dibutyl phthalate in a partial life-cycle test with zebrafish (Danio rerio) - Chen, Pengyu; Li, Song; Liu, Lei; Xu, Nan (Environmental toxicology and chemistry, 2015)
Using 17α‐ethinyl estradiol (EE2) and dibutyl phthalate (DBP) as a typical estrogen and phthalate ester, respectively, their combined in vivo effects on zebrafish (Danio rerio) were investigated from the juvenile state to the adult stage. The authors spiked EE2 (5 ng/L and 20 ng/L) and DBP (0.1 mg/L and 0.5 mg/L) either individually or in mixture. At 45 d postfertilization (dpf), the survival rate of zebrafish was comparable in all treatments. Dibutyl phthalate did not induce vitellogenin (VTG) synthesis, and no interaction was found between EE2 and DBP on VTG induction. At 90 dpf, both liver and gill were subject to more severe damage (lipid vacuoles of hepatocytes, amalgamation of gill lamellae, and clubbing at the tips of the secondary lamellae) when coexposed to these 2 chemicals, compared with single exposure. At 115 dpf, generally none of the binary mixture groups showed significantly different growth and sex ratios compared with the corresponding EE2 alone groups. In conclusion, no obvious interactions were detected between EE2 and DBP on the growth, VTG induction, or sex ratio of zebrafish, and they may act independently. However, the influence on morphology of gonad, liver, and gill induced by exposure to the mixture of EE2 and DBP was generally more potent than that by single exposure to EE2 or DBP, indicating the combined long‐term harmful effects of EE2 and DBP on the development of zebrafish. Environ Toxicol Chem 2015;34:518–526. © 2014 SETAC